After 228 years of being ignored or unplaced, Bibio lugens Thunberg, 1789 has its identity fixed (Diptera: Tabanidae: Pangoniinae) - Evenhuis, Neal L. (Zootaxa, 2017)
In preparing our world catalog of Bombyliidae (Evenhuis & Greathead 1999), we attempted to find any and all names that were or could possibly be attributed to the family. One of these in the latter category, Bibio lugens Thunberg, 1789, collected from the Cape of Good Hope in South Africa, was treated at the end of the catalog as Unplaced Species in Bombyliidae (Evenhuis & Greathead 1999: 528) since access to the type specimen was not feasible at the time and no images existed. All we could go on was its vague original description and placement of the name in Thunberg’s paper (1789: 89) in close association with other Bombyliidae.